(untitled) (Bangladesh Journal of Microbiology, 2008)
Total coliform (TC) and faecal coliform (FC) bacteria were analyzed in drinking water of Khairpur city. Ninty samples were collected from main reservoir (source), distribution line and consumer taps. pH and residual chlorine of water samples were also determined. For bacteriological analysis inductively membrane filtration (MF) method was used for total coliform (TC) as well as faecal (FC) coliform bacteria. All samples were found contaminated with total coliform (TC) and faecal coliform (FC) and the counts were higher than the maximum microbial contaminant level (MMCL) established by World Health Organization (WHO). It was observed that pH was within the limits of WHO standard (6.5-8.5). The residual chlorine was not detected in any sample of drinking water. Bacteriologically the water quality of the drinking water is unsatisfactory. Keywords: Coliform, Escherichia coli, Water quality, Contamination, Sanitation DOI: http://dx.doi.org/10.3329/bjm.v24i2.1266